Exercise-induced bronchial asthma in children: phenotypical polymorphysm - L. V. Kolyubakina; V. S. Khilchevska; O. G. Grygola (Kazimierz Wielki University, 2017)
Cluster analysis of a comprehensive clinical-anamnestic and paraclinical examination with the phenotype of exercise-induced bronchial asthma in schoolchildren depending on the type of acetylation. Heterogeneity of this cohort of patients has been found which requires a differential approach to administration of therapeutic measures